The Impact of Diction in the Introduction of Environmental Awareness on Employee Behaviour at Campus IBM Asmi Jakarta - Sompi, Pingkan Luciawati (Green Publisher Indonesia, 2025)
This study aims to analyze how word choice, or diction, in the introduction of environmental awareness (eco green) initiatives influences employee behavior at Campus IBM Asmi Jakarta. Language plays a critical role in shaping attitudes and actions, particularly in the context of sustainability efforts. This research examines how the selection of words and phrases affects perception, comprehension, and engagement with environmental policies among employees. The study also discusses best practices in communication strategies to foster a more environmentally responsible workforce. Employing an ecolinguistic approach and persuasive communication theory, this research explores the role of language in enhancing pro-environmental awareness and actions within the organizational environment. The methodology includes discourse analysis of environmental campaign materials used by the institution, as well as a survey of employees regarding the impact of these communications on their behaviors. The results indicate that the use of positive and persuasive language is more effective in increasing employee participation in environmentally friendly practices than instructive or imperative language. These findings have significant implications for the development of corporate communication strategies that support environmental sustainability.